The relationship between socioeconomic status and fine motor skills among six years old preschool children / Noreriani Sabturani - Sabturani, Noreriani (2013)
Fine motor skills are action involve small muscles using hand and fingers for precise movements. Fine motor skills is important especially in six years old preschool children because they are engaging with eye hand coordination, in hand coordination and bilateral especially in handwriting and drawing activities. Socioeconomic status (SES) is one of the factor may affect children fine motor skills development because children from low SES was high prevalence of growth restriction due to inequalities lifestyle and may associated with delay in motor development. The purpose of this study was to identify the relationship between fine motor skills and SES among six years old preschool children. A total of 168 children (male=84, female=84) aged six years old preschool children participated in this study. They were divided into three groups based on parent’s income which were known as low income group, moderate income group and high income group. McCarron Neuromuscular Development (MAND, 1975) was used to measure fine motor skills. The result showed that there was significant different in fine motor skills between groups (ρ<().05). However, there was no significant different between fine motor skills and gender (ρ >().05). Moreover, there was significant relationship between fine motor skills and SES { ρ <0.05). Children from low SES have low fine motor skills performance compared to higher SES. Overall, the result of the current study showed that gap in SES. has influence fine motor skills development.